2019
DOI: 10.1016/j.cub.2018.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Noemi Controls Production of Flavonoid Pigments and Fruit Acidity and Illustrates the Domestication Routes of Modern Citrus Varieties

Abstract: Highlights d Noemi is essential for the production of flavonoid pigments in citrus d Noemi is essential for the regulation of fruit acidity in citrus d Retrotransposons are associated with the acidless phenotype in commercial varieties d A specific ancient mutation retraces the steps of citrus history and cultivation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 32 publications
2
72
0
Order By: Relevance
“…However, the target proteins of MdbHLH3 and MdCIbHLH1 differ in their functions in regulating malate vs. anthocyanin accumulation. Recent studies have identified Noemi , encoding a bHLH transcription factor, controls two co-evolved traits in citrus, fruit acidity and anthocyanin levels (Butelli et al, 2019; Zhu et al, 2019). Our findings here suggest that Noemi might regulate fruit acidity and anthocyanin levels via a pathway similar to MdbHLH3-MdMYB1 (Xie et al, 2012; Hu et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the target proteins of MdbHLH3 and MdCIbHLH1 differ in their functions in regulating malate vs. anthocyanin accumulation. Recent studies have identified Noemi , encoding a bHLH transcription factor, controls two co-evolved traits in citrus, fruit acidity and anthocyanin levels (Butelli et al, 2019; Zhu et al, 2019). Our findings here suggest that Noemi might regulate fruit acidity and anthocyanin levels via a pathway similar to MdbHLH3-MdMYB1 (Xie et al, 2012; Hu et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Malate, as a key metabolite, plays a vital role in plant metabolism, pH homeostasis, nutrient uptake, osmotic adjustment and abiotic stress resistance (Fernie and Martinoia, 2009; Finkemeier and Sweetlove, 2009; Bai et al, 2015; Hu et al, 2017). Cellular malate accumulation also largely determines the acidity and perception of sweetness of fleshy fruits and their processed products (Yao et al, 2007; Ye et al, 2017; Butelli et al, 2019; Ma et al, 2019). The majority of malate in the parenchyma cells of fleshy fruits is in the vacuole (Yamaki, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Key to its domestication must have been its visual appeal -imagine the shock of something so yellow or orange -and also its taste. In a paper by Butelli et al [1] published in a recent issue of Current Biology we can suddenly understand how colour and taste are closely tied to each other, by job-sharing the same basichelix-loop-helix (bHLH) transcription factor called Noemi.…”
mentioning
confidence: 99%
“…This trait is linked to fruit acidity; the loss of anthocyanin-linked colour correlates with a loss of fruit acid, with the pH of the fruit cells rising as much as 3 pH units, from pH 2.5 to 5.5! Butelli's paper [1] describes mutations in Noemi, a bHLH transcription factor that regulates both flavonoids and acidity, which have been selected for during the domestication of citrus. Selection may have been first on the appearance of purity (white flowers and bright yellow fruit) for religious rituals.…”
mentioning
confidence: 99%
See 1 more Smart Citation